THE CRISIS OF MEANING IN CONTEMPORARY SOCIETY: AN ANALYSIS FROM THE PERSPECTIVE OF LUDWIG WITTGENSTEIN’S SOCIAL PHILOSOPHY (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the phenomenon of the crisis of meaning in contemporary society from the perspective of Ludwig Wittgenstein’s social philosophy. In the context of rapid social transformation, digital communication, and the fragmentation of shared cultural frameworks, the problem of meaning has become increasingly acute. Drawing on Wittgenstein’s concepts of “language games,” “forms of life,” and the social use of language, the study argues that the crisis of meaning emerges not from a lack of information, but from the disruption of common linguistic and social practices. The paper examines how the erosion of shared norms and practices leads to ambiguity, miscommunication, and the weakening of social cohesion. The analysis demonstrates that meaning, in Wittgenstein’s view, is grounded in collective forms of life and cannot be sustained outside stable social contexts. The findings suggest that addressing the crisis of meaning requires the restoration of meaningful social practices and ethical frameworks rather than purely technical or informational solutions. The study contributes to contemporary social and philosophical debates on meaning, communication, and cultural continuity.